Precise Electrocardiogram Signal Analysis Using ResNet, DenseNet, and XceptionNet Models in Autistic Children - Yunidar Yunidar; Melinda Melinda; Albahri Albahri; Hanum Aulia Ramadhani; Herlina Dimiati; Nurlida Basir (Poltekkes Kemenkes Surabaya, 2026)
Indexed by Scopus